Econometrics of the impact of financial inclusion on banking stability in Iraq - علي الخزرجي ثريا عبد الرحيم; سعيد الأعرجي صبيان طارق (Journal of Economics and Administrative Sciences, 2020)
Financial inclusion refers to the access of financial services at low cost and high-quality from the formal financial sector to all segments of society, especially marginalized groups, and then use and benefit from them. Financial inclusion is also associated with banking stability, as well as with financial integrity and financial protection for the consumer, therefore, it achieves a number of objectives, the most important of which is to support and enhance banking stability. This is what made it attract the attention of many countries and central banks recently. The study aims to show the impact of financial inclusion indicators on banking stability in a sample consisting of 32 private banks in the Iraqi banking sector for the period from the first half of 2016 to the second half of 2018, according to the hypothesis of the study, which went on to have a positive impact of financial inclusion indicators on Bank stability index, as the study was based on the data of the payments department of the Central Bank of Iraq as well as periodic reports of the sample banks. Using Panel Data Dynamic, specifically the generalized method of moments -GMM, the results did not fully accept the hypothesis and some indicators of financial inclusion such as the number of bank branches and the size of deposits negative effect on banking stability. In addition, the impact of money credit and the number of bank accounts for the corporate on the stability index is not established, except for the number of bank accounts for individuals, the results of the estimate showed a significant positive effect.